Rendezvous technique for recanalization of long-segmental chronic total occlusion above the knee following unsuccessful standard angioplasty. (April 2016) - Cao, Jun; Lu, Hai-Tao; Wei, Li-Ming; Zhao, Jun-Gong; Zhu, Yue-Qi
Purpose: To assess the technical feasibility and efficacy of the rendezvous technique, a type of subintimal retrograde wiring, for the treatment of long-segmental chronic total occlusions above the knee following unsuccessful standard angioplasty. Methods: The rendezvous technique was attempted in eight limbs of eight patients with chronic total occlusions above the knee after standard angioplasty failed. The clinical symptoms and ankle-brachial index were compared before and after the procedure. At follow-up, pain relief, wound healing, limb salvage, and the presence of restenosis of the target vessels were evaluated. Results: The rendezvous technique was performed successfully in seven patients (87.5%) and failed in one patient (12.5%). Foot pain improved in all seven patients who underwent successful treatment, with ankle-brachial indexes improving from 0.23 ± 0.13 before to 0.71 ± 0.09 after the procedure ( P < 0.001). At the end of the follow-up period, the visual analogue scale improved from 6.86 ± 1.57 to 1.57 ± 1.27 ( P < 0.001). Non-healing ulcers in three patients either healed (n = 2) or improved (n = 1). No major amputation was necessary. Kaplan–Meier analyses revealed that stenosis-free rate was 83.3% at six months and 41.7% at 12 months. Conclusion: The rendezvous technique is a feasible and effective treatment for chronic total occlusions above the knee when standard angioplasty fails.